2009
DOI: 10.1007/s12017-009-8105-y
|View full text |Cite
|
Sign up to set email alerts
|

HTR2A is Associated with SSRI Response in Major Depressive Disorder in a Japanese Cohort

Abstract: Several recent investigations reported that the serotonin 2A receptor gene (HTR2A) was associated with selective serotonin reuptake inhibitors (SSRIs) in major depressive disorder. There have also been two reported association analyses of HTR2A with SSRI response in Japanese MDD patients, but the results were rather inconsistent and both studies had the problem of small sample sizes. Therefore, we conducted a replication association study using a sample larger than those in the two original Japanese studies (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 26 publications
0
27
1
1
Order By: Relevance
“…Indeed, rs7333412, rs7324017, rs1923882 and rs7997012 (Peters et al 2009) are located in this region and were associated with antidepressant response in the STAR*D sample. Several other studies investigated rs7997012 with negative results (Illi et al 2009;Kishi et al 2009;Perlis et al 2009;Uher et al 2009;Horstmann et al 2010), although none of these included samples as large as the STAR*D study. The effect of rs7997012 and rs6313 on antidepressant efficacy was confirmed by the most recent meta-analysis (Lin et al 2014).…”
Section: Genetic Polymorphisms Different Polymorphismsmentioning
confidence: 99%
“…Indeed, rs7333412, rs7324017, rs1923882 and rs7997012 (Peters et al 2009) are located in this region and were associated with antidepressant response in the STAR*D sample. Several other studies investigated rs7997012 with negative results (Illi et al 2009;Kishi et al 2009;Perlis et al 2009;Uher et al 2009;Horstmann et al 2010), although none of these included samples as large as the STAR*D study. The effect of rs7997012 and rs6313 on antidepressant efficacy was confirmed by the most recent meta-analysis (Lin et al 2014).…”
Section: Genetic Polymorphisms Different Polymorphismsmentioning
confidence: 99%
“…Authors of that study also concluded that a genetic factor may contribute to the etiology of sleep bruxism (11). In addition, the HTR2A gene has been associated with other psychological and systemic conditions, including schizophrenia (12), obsessive compulsive disorders (13), and depressive disorders as well as with psychosomatic symptoms (14). It was also found, in the literature, that 5HT2A is known as the 5-HT2 gene.…”
Section: Introductionmentioning
confidence: 97%
“…For example, the TPH2 gene may have an important effect on susceptibility to suicidal behavior in MDD patients [41] and on the therapeutic response to antidepressants [36]. The correlation between functional polymorphisms associated with serotonergic neurotransmission and antidepressant treatment response has been widely studied [42,43,44]. Numerous studies have suggested that these serotonergic candidate genes may influence the therapeutic response in an interactive manner [23,45].…”
Section: Discussionmentioning
confidence: 99%